2020
DOI: 10.3390/s20143957
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Growing Stem Volume of the Planted Forest Using the General Linear Model and Time Series Quad-Polarimetric SAR Images

Abstract: Increasing the area of planted forests is rather important for compensation the loss of natural forests and slowing down the global warming. Forest growing stem volume (GSV) is a key indicator for monitoring and evaluating the quality of planted forest. To improve the accuracy of planted forest GSV located in south China, four L-band ALOS PALSAR-2 quad-polarimetric synthetic aperture radar (SAR) images were acquired from June to September with short intervals. Polarimetric characteristics (un-fused and fused) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Previous studies have demonstrated the strong correlation between forest aboveground biomass (AGB) and vegetation indices derived from optical imagery, indicating their potential for mapping forest AGB [3][4][5][6][7][8][13][14][15]36]. Similarly, our study also confirmed the feasibility of using optical remote sensing data for mapping forest AGB.…”
Section: Factors Affecting Transferabilitysupporting
confidence: 85%
See 2 more Smart Citations
“…Previous studies have demonstrated the strong correlation between forest aboveground biomass (AGB) and vegetation indices derived from optical imagery, indicating their potential for mapping forest AGB [3][4][5][6][7][8][13][14][15]36]. Similarly, our study also confirmed the feasibility of using optical remote sensing data for mapping forest AGB.…”
Section: Factors Affecting Transferabilitysupporting
confidence: 85%
“…Regarded as the largest organic carbon reservoir, forests play an indispensable role in promoting the global carbon cycle and buffering global warming [1][2][3]. Forest aboveground biomass (AGB) is viewed as one of the most important indicators for assessing the carbon sequestration capacity [4][5][6][7]. Therefore, it is meaningful to accurately and efficiently map the forest AGB and obtain the spatial distribution information for guiding rational forest management activities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study assesses that, using multitemporal L-band SAR acquisitions, the %RMSE (percentage of mean AGB) improves from 135% to 89% for Mondah and from around 60% to 45-50% for Lope forest test sites. Using four ALOS-2 acquisitions over a Chinese fir-dominated forest, the AGB estimation accuracy improved from a %RMSE of 33.8% for a single acquisition to 24.4% when multitemporal data were used (Long et al, 2020). However, over a Pine and Eucalyptusdominated semiarid forest in Australia, Tanase et al (2014) report that the multitemporal approach provides more reliable AGB estimates but did not improve the AGB estimation accuracy significantly.…”
Section: Multitemporal Agb Retrievalmentioning
confidence: 92%
“…Microwave radar is an advanced active remote sensing technology not easily affected by climatic factors, such as clouds, fog, and solar radiation, and can realize all-weather earth observations [31][32][33]. Depending on the wavelength and frequency, microwave radar signals can penetrate the forest canopy to different degrees and obtain comprehensive in-formation on the forest structure at different levels and orientations [34][35][36][37][38][39]. The microwave radar remote sensing technologies commonly used in FSV estimation include synthetic aperture radar (SAR), interferometric radar (InSAR), and polarization interferomet-ric radar (PolInSAR) [40,41].…”
Section: Introductionmentioning
confidence: 99%